The Influence of Leadership, Organizational Climate, and Work Motivation on Employee’s Performance - Italiani, Natalia; Musmuliadi, Musmuliadi; Diju, Augustine (Interdisciplinary Social Studies, 2022)
Employee performance is one of the main factors that affect the progress of the agency, so the higher or better the employee's performance, the easier the agency's goals will be achieved. A way that can be applied to improve employee performance is to apply effective leadership to employees.  In addition to leadership, the organizational climate also affects the behavior of a worker. Then, in order to achieve organizational goals, employees need motivation to be more active in working so that work results become better and more punctual. This study aims to determine the influence of leadership, organizational climate, and work motivation on the performance of employees of the West Kutai Regency Inspectorate, both separately and simultaneously. The approach used in this study is a  quantitative approach. The data sources used in this study are primary data obtained from the results of direct interviews with respondents and secondary data obtained by collecting information from parties related to the West Kutai Regency Inspectorate. Leadership, organizational climate and work motivation have a positive and significant influence on the performance of employees of the West Kutai Regency Regional Inspectorate, therefore the West Kutai Regency Regional Inspectorate needs to continue to maintain and improve these variables.